Host Lipid Rafts as the Gates for Listeria monocytogenes Infection: A Mini-Review - Tsai, Yu-Huan; Chen, Wei-Lin (Frontiers in Immunology, 2020)
Listeria monocytogenes is a Gram positive foodborne bacterial pathogen capable of interacting and crossing intestinal barrier, blood-brain barrier, and placental barrier to cause deadly infection with high mortality. L. monocytogenes is an intracellular pathogen characterized by its ability to enter into non-phagocytic cells. Expression of the cytolysin listeriolysin O has been shown to be the main virulence determinant in vitro and in vivo in mouse models. L. monocytogenes can also perform cell-to-cell spreading using actin-rich membrane protrusions to infect neighboring cells, which also constitutes an important strategy for infection. These events including entry into host cells, interaction between listeriolysin O and host plasma membrane, and bacterial cell-to-cell spreading have been demonstrated to implicate the cholesterol-rich lipid rafts or molecules in these microdomains in the host plasma membrane in vitro with tissue culture models. Here we review the contribution of lipid rafts on plasma membrane to L. monocytogenes infection.